THE EVOLUTION OF THE ENGLISH LANGUAGE: FROM OLD ENGLISH TO MODERN ENGLISH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The English language is one of the most widely spoken and influential languages in the world today, serving as a global lingua franca across industries, education, and culture. However, the journey of English from its historical origins to its modern form is marked by significant changes in vocabulary, grammar, and pronunciation. This article explores the major phases of English’s evolution, highlighting the historical foundations and contemporary developments shaping the language we use today.